Cutaneous Manifestations of Thyroid Disease: A Case of Thyroid-Induced Myxedema. (30th November 2011) - Shroff, Anjali; Simpson, Gregory
Abstract : The cutaneous manifestations of thyroid disease can be present in the hair, nails, and local or diffuse locations throughout the skin. Traditionally, thyroid-associated mucin deposition is present in a pretibial location on bilateral lower legs. We present a case of a growing plaque on the lower back of a 10-year-old girl, whose appearance coincided with a recent diagnosis of Hashimoto's thyroiditis.